Petunia. - Duvoisin, Roger, 1900- ([New York, Random House, 1973)
Petunia, the goose, learns that possessing knowledge involves more than just carrying a book around under her wing.
"Knopf/Pantheon pinweel books."
Reprint of the 1st ed. published by Knopf, New York.
Keywords: Petunia (Fictitious character : Duvoisin); Geese -- Fiction